Pancasila dan Deradikalisasi Berbasis Agama - Ridwan, Nur Khalik (Jurnal Pendidikan Islam, 2013)
Pancasila is the state foundation and national philosophy that is received by the majority of the Indonesian people. Religious education with no concept of Pancasila makes only the generation of separation instead of national integration that is needed by the nation of Indonesia. Religious education must be the education of sensitive peace, sensitive to people’s issues and social justice that is as an important part of the Pancasila and the needs of our nation. Religious education becomes an important part to increase faith, to have a good nation, and to make a good beliver and patriotic.